Handover Using the Introduction, Situation, Background, Assessment, and Recommendation (ISBAR) Checklist Improves Nurses’ Self-Efficacy - Yulianti, Lena; Putra, Kuswantoro Rusca; Supriati, Lilik; Utami, Yulian Wiji (Department of Nursing, Faculty of Health Sciencce, Universitas Brawijaya, 2025)
Handover is a crucial aspect of patient transfer to ensure patient safety and reduce adverse events. The Introduction, Situation, Background, Assessment, and Recommendation (ISBAR) method is a standardized communication approach recommended to improve handover quality. Nurses require adequate self-efficacy not only to deliver handover information but also to receive it effectively to ensure continuity of care. Continuity of patient treatment is associated with improved patient outcomes and reduced length of hospital stay. This study aimed to evaluate the effectiveness of a modified ISBAR checklist, adapted from the existing patient transfer form and developed by the researcher, in improving nurses’ self-efficacy during patient transfers from the Emergency Department (ED) to the High Care Unit and Intensive Care Unit (HCU–ICU). A pre-experimental study using a one-group pretest–posttest design was conducted. Ten ED nurses applied the modified ISBAR checklist during handovers to HCU–ICU nurses. A total of 40 nurses working in HCU and ICU settings participated as respondents. Nurses’ self-efficacy was measured using the General Self-Efficacy Scale before and after implementation of the ISBAR checklist. The results showed a statistically significant improvement in nurses’ self-efficacy following the use of the ISBAR checklist (p = 0.000; p < 0.05), based on Wilcoxon test analysis. The effectiveness analysis yielded an N-gain score of 0.388, indicating a moderate level of effectiveness. In conclusion, the ISBAR checklist effectively enhances nurses’ self-efficacy during inter-unit handover, supporting structured communication, continuity of care, and safer patient transfers in high-acuity clinical settings.